LKB1 Mediates the Development of Conventional and Innate T Cells via AMP-Dependent Kinase Autonomous Pathways - Zarrouk, Marouan (Public Library of Science, 2013)
The present study has examined the role of the serine/threonine kinase LKB1 in the survival and differentiation of CD4/8 double positive thymocytes. LKB1-null DPs can respond to signals from the mature α/β T-cell-antigen receptor and initiate positive selection. However, in the absence of LKB1, thymocytes fail to mature to conventional single positive cells causing severe lymphopenia in the peripheral lymphoid tissues. LKB1 thus appears to be dispensable for positive selection but important for the maturation of positively selected thymocytes. LKB1 also strikingly prevented the development of invariant Vα14 NKT cells and innate TCR αβ gut lymphocytes. Previous studies with gain of function mutants have suggested that the role of LKB1 in T cell development is mediated by its substrate the AMP-activated protein kinase (AMPK). The present study now analyses the impact of AMPK deletion in DP thymocytes and shows that the role of LKB1 during the development of both conventional and innate T cells is mediated by AMPK-independent pathways.